Base Shear Struktur Beton Bertulang Yang Menggunakan Base Isolator Akibat Beban Gempa Dengan Menggunakan Etabs - Dicky N. Nggaba; Partogi H Simatupang; A. Hidayat Rizal (Universitas Nusa Cendana, 2021)
The sudden release of energy within earth creates seismic waves on earth’s surface that is earthquake. This research was carried out using a base isolator type of HDR with Certification Number MVBR-0516 (XO.3R) to reduce base shear, displacement and internal forces acting on the structure. This study uses time history analysis method with some earthquake loads in the form of acceleration acceleration. The objectives of the study were to determine the base shear of a reinforced concrete structure building using a base isolator and without using a base insulator. The results of this study indicate the use of base insulators reduces base shear by about 20% -67% and 14% -70.5% for earthquakes in the x direction to the east and west. Meanwhile, in the y direction earthquake, it was around 43% -70% and 43% -62% to the south and north